Five day course in thinking - "Bono, De Edward" (London; Vermilion, 2016)
Based on the tenet that an error can lead to the right decision, de Bono guides the reader through a series of non-mathematical problems and puzzles, all designed to help us analyse our personal style of thinking, work out its strengths and weaknesses, and to consider the potential methods that we never use. There are three courses, each five days long and each created to focus on a different style of thinking, A true life-changer, this book will have you thinking in ways that you never thought were possible
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Problem Solving